Pecteilis korigadensis (Orchidaceae: Orchidoideae), a new terrestrial orchid from the northern Western Ghats, India - Jalal, Jeewan Singh; Jayanthi, Janakiraman (Phytotaxa, 2019)
The Western Ghats are a global biodiversity hotspot and treasure trove of biological diversity. They harbour many endemic species of flowering plants and also form an important centre of evolution of economically important domesticated plant species. Certain identified parts of the Western Ghats have been included in the UNESCO World Natural Heritage list because they are considered as cradle of evolution (MOEF&CC 2015). Although the Western Ghats cover only 5% of the country’s total land area, they also are a habitat for more than 7000 or 27% of the total plant species in India. The number of endemic plant species in the Western Ghats is estimated to be 2253 (Nayar et al. 2014).This natural landscape exhibits wide variation in rainfall coupled with complex geography, forming a vast diversity of vegetation types (Chitale et al. 2014) and supporting a rich orchid diversity. To date, 306 species of orchids have been recorded from the Western Ghats (Nayar et al. 2014), nearly one-third of them endemic. These orchids are mainly found in semi-evergreen forest, shola forest and lateritic plateaus. The Western Ghats region has been a site of intense taxonomic activity, and due to plant explorations by several researchers there has been discovery of many new species and reports (Kumar et al. 2016, Jayanthi et al. 2017). In the past fifty years (1950–2000), more than 27 species of orchids have been discovered in the Western Ghats, and the species discovery curve has not yet attained an asymptote (Aravind et al., 2007).